PEMBUATAN BIODIESEL DARI LEMAK IKAN PATIN(Pangasius sp) DENGAN RADIASI GELOMBANG MIKRO - Tanjung, Albayssag Faisal; -, Alimuddin; Yusuf, Bohari (Jurusan Kimia FMIPA UNMUL, 2016)
The research about made biodiesel from fat of patin fish (Pangasius sp) as raw material and known influence time exposure microwave radiation to concentration biodiesel that was produced have been done.Fat of patin fish heated to get oil extract. The oil extract was refluxed with methanol as reactant and H2SO4 as catalyst for 120 minute. Then transesterified with methanol as reactant and NaOH as catalyst with different time that was for 2, 4, 6, 8, and 10 minutes. The high product of biodiesel is 87,2 b/v that was exposured microwave radiation for 8 minutes. To knew kind of methyl ester in biodiesel used GC-MS and the high concentration of methyl ester in biodiesel is methyl oleat with concentration 24,74%.